2010
DOI: 10.1007/s10620-010-1498-5
|View full text |Cite
|
Sign up to set email alerts
|

Accidental Occupational Injuries to Endoscopy Personnel in a High-Volume Endoscopy Suite During the Last Decade: Mechanisms, Workplace Hazards, and Proposed Remediation

Abstract: Potentially correctable design flaws may frequently contribute to accidents in endoscopy suites, including: bulky overhead video monitors, too narrow doors for extra-wide stretchers, absence of slip-resistant flooring, and wires exposed above the floor.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 24 publications
0
8
0
Order By: Relevance
“…Other injuries have been documented including tripping on exposed wires, hands crushed against doorways when moving patients, slips/falls on wet floors/spills, and musculoskeletal injuries related to turning patients 33. Some of these injuries are at least partially inherent to the designs of the procedure rooms.…”
Section: Preventionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other injuries have been documented including tripping on exposed wires, hands crushed against doorways when moving patients, slips/falls on wet floors/spills, and musculoskeletal injuries related to turning patients 33. Some of these injuries are at least partially inherent to the designs of the procedure rooms.…”
Section: Preventionmentioning
confidence: 99%
“…Doors should be widened to easily accommodate beds up to 43 inches wide, and 2 staff should be utilized to move heavier patients 25. Studies have documented injuries from tripping over cords/cautery cords, oxygen tubing, etc.,33,34 which accounts for an estimated 450 to 600 falls/year in the United States 34. Nonslip flooring should be utilized.…”
Section: Preventionmentioning
confidence: 99%
“…Other studies have highlighted accidents that resulted in musculoskeletal injuries, including crushed hand against the doorway during patient transport, head strike on mounted monitors, slip and fall on wet floors, back and wrist sprain while breaking a fall, and trip and fall over exposed wires, cords and oxygen tubing [ 35 , 36 ]. Moreover, it is estimated that, on average, endoscopic-related musculoskeletal injuries result in 6 lost working days and 9 restricted work days [ 35 , 36 ]. Thus, the need for ensuring proper ergonomic practice impacts endoscopic personnel, patients, and hospital systems.…”
Section: Musculoskeletal Injuriesmentioning
confidence: 99%
“…Treatments for the various musculoskeletal injuries sustained ranged from as simple as acetaminophen and ibuprofen therapy for a few days to as severe as open surgical reduction and fixation of fractures. Of 17 endoscopists and staff who sustained endoscopy-associated musculoskeletal injuries, 7 were treated with only acetaminophen or ibuprofen for about 5-10 days; 4 individuals had a combination therapy with acetaminophen or ibuprofen and a plaster cast or digit/wrist splinting; 1 person was treated with a knee immobilizer and 7 days of ibuprofen for her left knee contusion due to a slip and fall on a wet floor; another individual had an open surgical reduction and fixation for right-hand metacarpal and digit fractures sustained after a trip and fall over exposed wires on the floor; and another individual required hydrocodone, corticosteroid injections to a herniated disc and intensive physical therapy for back injury while positioning a patient during endoscopy [ 35 , 36 ]. Ridtitid et al reported that only 55% of injured endoscopists applied practice modifications in response to injuries [ 23 ].…”
Section: Musculoskeletal Injuriesmentioning
confidence: 99%
“…The situation described has been reported in the literature 1,2 and was considered when AORN revised its “Recommended practices for a safe environment of care.” 3 The revised recommended practices document recommends using an extension cord or a multiple outlet cord that has been attached to a stand or a cart to reduce the risk of personnel tripping over electrical cords 3 . AORN no longer recommends changing the cord on a piece of equipment as the first method to eliminate a tripping hazard presented by a cord not laying flat on the floor because it may negate the warranty and increase the liability of using the equipment 3,4 .…”
Section: Use Of Extension Cords In the Ormentioning
confidence: 99%